Detectability of space debris objects in the infrared spectrum. (June 2022) - Schubert, M.; Böttcher, L.; Gamper, E.; Wagner, P.; Stoll, E.
Abstract: While the quantity of space debris objects is steadily increasing, the necessity for space- or ground-based systems observing and cataloguing these objects grows as well. In principle, observations can be made by radar or optically by telescopes. Optical observations have various advantages over radar, such as low purchase and operating costs combined with high precision. A major disadvantage of optical observations in the visual spectrum, however, is their availability, as they depend on clear skies and can generally only be operated in the twilight phase, i.e. about four to 6 h per day. However, if the optical observations are shifted into the infrared range, it seems possible to observe objects in the Earth's shadow. Depending on material properties and trajectory, the object can also emit infrared radiation in the Earth's shadow, be it reflected thermal radiation from the Earth or its own thermal radiation due to the material temperature. Thus, it seems possible that the number of optical detections (space- or ground-based) could potentially increase by additional detections in the infrared range. Also, the sensitivity for some objects in the infrared range may be better than in the visual-optical range. In order to evaluate the general feasibility of such observations in the infrared range, a sensor model has been developed simulating the characteristics of real infrared sensors. This model was connected to the ESA software tool PROOF. Thereby, reference object populations and corresponding detections in the visible range were simulated and compared in succession with the implemented sensor model. Performing an exemplary simulation, it was indeed possible to achieve additional detections in the infrared spectrum that were not obtained in the visual spectrum. However, the observations were only simulated over a time span of 24 h. It is expected that the number of objects that are only detected in the infrared spectrum decreases significantly if a longer period would be simulated. Additionally, the sensor that allowed the best results represents one of the most advanced existing sensors for the infrared spectrum, developed for the James Webb Telescope. In comparison, a commercially available sensor showed clearly inferior results. Highlights: Analyzing the usage of the infrared spectrum to improve Space Debris observations. Cutting-edge infrared sensors can detect significant numbers of objects. Simulations using commercially available sensors generate less optimistic results.